Osteoporosis in Surgical Menopause - Kabir, Farhana; Jahan, Nasim; Sultana, Nayma (Journal of Bangladesh Society of Physiologist, 2011)
Background: Osteoporosis in both surgical and natural menopausal women are common health hazards all over the world. And the surgical menopausal women may have the greater chance of this disorder than those of natural menopausal women. Objective: To observe osteoporotic changes in both surgical and natural menopausal women in Bangladesh. Method: This Cross sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College, Dhaka between 1st January 2010 to 31st December 2010. A total number of 60 female subjects were included in this study. Among them 30 surgical menopausal women age ranged from 45-55 years were included in the study group (Group B) and 30 natural menopausal women age ranged from 50-60 years were taken as control (Group A). All the menopausal women were selected from Out Patient Department (OPD) of Gynaecology and Obstetrics, Sir Salimullah Medical College and Mitford Hospital. Estimation of serum estrogen level by microparticle enzyme immunoassay (MEIA) method and T- score was obtained by Dual energy X-ray absorptiometry of both natural and surgical menopausal women were done. The statistical analysis was done by using appropriate method as applicable. Results: In this study T- score of both spinal and femoral neck bone were significantly (p<0.001) lower in surgical menopausal women than those of natural menopausal women. Again, mean serum estrogen level was significantly (p<0.001) lower in surgical menopausal women than that of natural menopausal women. Conclusion: The present study revealed that surgical menopausal women have greater chance of osteoporosis than those of natural menopausal women. Key words: Menopause; Bone mineral density; Osteoporosis. DOI: http://dx.doi.org/10.3329/jbsp.v6i1.8083 J Bangladesh Soc Physiol. 2011 June; 6(1): 39-44